A case of pulmonary arteriovenous malformation: role of interventional radiology in diagnosis and treatment - Sharma, Pranav (Ann Transl Med, 2017)
Pulmonary arterio-venous malformations (PAVMs) are abnormal pulmonary arteries and pulmonary veins communicating directly without interposition of a capillary bed and about 80–90% of patients with PAVMs eventually may present with hereditary hemorrhagic telangiectasia (HHT), remaining ones are sporadic cases. On the other hand, about 15–35% of HHT patients may present with PAVMs. The PAVMs have a tendency to grow and increase in size over time and various factors like puberty, pregnancy and pulmonary arterial hypertension (PAH) affect growth. This condition needs early diagnosis, aggressive management and vigilant follow up. Our article aims to review pulmonary AVMs as a rare cause of strokes in young patients. We will discuss the clinical presentation, diagnosis, complications, the therapeutic options and the follow up.